Prediction of solute transport in a heterogeneous aquifer utilizing hydraulic conductivity and specific storage tomograms. Issue 7 (19th July 2015) - Jiménez, S.; Brauchler, R.; Hu, R.; Hu, L.; Schmidt, S.; Ptak, T.; Bayer, P.
Abstract: A sequential procedure of hydraulic tomographical inversion is applied to characterize at high resolution the spatial heterogeneity of hydraulic conductivity and specific storage at the field test site Stegemühle, Germany. The shallow aquifer at this site is examined by five short‐term multilevel pumping tests with 30 pumping‐observation pairs between two wells. Utilizing travel time diagnostics of the recorded pressure response curves, fast eikonal‐based inversion is shown to deliver insight into the sedimentary structures. Thus, the structural information from the generated travel time tomogram is exploited to constrain full calibration of the pressure response curves. Based on lateral extrapolation from the measured inter‐well profile, a three‐dimensional reconstruction of the aquifer is obtained. It is demonstrated that calibration of spatially variable specific storage in addition to hydraulic conductivity can improve the fitting of the model while the structural features are only slightly changed. At the field site, two tracer tests with uranine and sodium‐naphthionate were also performed and their concentrations were monitored for 2 months. The measured tracer breakthrough curves are employed for independent validation of the hydraulic tomographical reconstruction. It is demonstrated that major features of the observed solute transport can be reproduced, and structures relevant for macrodispersive tracer spreading could be resolved. However, for the mildly heterogeneous aquifer, the tracer breakthrough curves can also be approximated by a simplified homogeneous model with higher dispersivity. Therefore, improved validation results that capture specific characteristics of the breakthrough curves would require additional hydraulic measurements. Key Points: Sequential hydraulic tomographical inversion Combination of structural information and full signal inversion Tracer tests used as independent validation